Pengaruh Metode Sosiodrama Berbantuan Media Audio Visual Terhadap Kemampuan Komunikasi Anak Usia 5-6 Tahun - Kameliastri; Parwoto; Herman (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research aims to determine the effect of the sociodrama method assisted by audio-visual media on the communication skills of young children. The research approach used is a quantitative approach with a Quasi Experimental Design research type. The population in this study was 18 children. The sample in this study consisted of 16 children, divided into 8 children as the experimental group and 8 children as the control group. The data analysis techniques used are descriptive statistical analysis and non-parametric analysis. The communication abilities of children for the experimental group showed that it was and the sig (2-tailed) value was 0.011 <0.05, so it can be concluded that there were differences in the communication abilities of children in the experimental group before and after being given treatment. Based on the research results, it can be concluded that the communication skills of children who were treated with the sociodrama method in the experimental group were better than the control group. So, it can be concluded that the sociodrama method has a significant influence on the communication skills of children aged 5-6 years at Al Amanah Nur Hamriani Kindergarten.